„Handlująca Warszawa” w drugiej połowie XIX wieku, czyli słownictwo z zakresu handlu w Lalce Bolesława Prusa - Pihan-Kijasowa, Alicja (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The vocabulary concerning trade has been accompanying human activity for centuries, thus, it is no wonder that the core of the Polish vocabulary in this thematic field stems from Proto-Slavic times (e.g., cena [price], darmo [free], kupić [buy], pieniądz [money], płacić [pay]). On the Polish soil, we can observe the processes increasing the pool of this vocabulary: these are vernacular derivative processes and borrowings of foreign words. In this way, the contemporary dictionary of the thematic field TRADE has been formed. Lalka (“The Doll”) by Bolesław Prus, a novel representing classical realism, is rooted in Polish social and economic realities of the second half of the 19th century – it depicts the arrival and strengthening of capitalism, mainly in the sphere of trade. This implies the introduction into the novel of an extensive, composed of over 300 units, lexicon which groups the words that, by definition or by context, are connected with this sphere of the protagonists’ activity. The centre of the discussed thematic field is formed by word fields of the main notions from this sphere, such as: handel [trade], sklep [shop], sprzedawca [shop attendant], kupujący [buyer], kupować [buy], sprzedawać [sell], płacić [pay], pieniądz [money], cena [price]. Being entangled in various lexical contexts, they also show the contemporary scope of meaning of individual words as well as the possibility to modify them by lexical environment.